1985
DOI: 10.1136/jcp.38.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural changes of the human proximal small intestine after cytotoxic therapy.

Abstract: SUMMARY The effects of cytotoxic therapy on the structure and function of the proximal jejunum were studied in six patients receiving intravenous cyclophosphamide (300 mg/M2), methotrexate (40 mg/M2), and 5-fluorouracil (600 mg/M2) as adjuvant therapy for breast cancer. Using a steady state, triple lumen tube perfusion system the absorption of water and electrolytes was measured before and 48 h after administration of the cytotoxic agents. Jejunal biopsies were obtained at each perfusion. Median (range) water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…Several studies, both in humans and rodents, have showed a correlation between the changes in the expression and/or activities of the brushborder glycohydrolytic enzymes and the severity of the gastrointestinal damage caused by 5-FU [5,55] . Cunninghan et al [56] failed to show any abnormality of disaccharidase activities in jejunal biopsies collected from patients 48 h after receiving a single intravenous dose of 5-FU. The inconsistency between the results of the present study and the Cunninghan work may be explained on the basis of the different regimen of 5-FU administration used, which induced a different pattern of histological alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, both in humans and rodents, have showed a correlation between the changes in the expression and/or activities of the brushborder glycohydrolytic enzymes and the severity of the gastrointestinal damage caused by 5-FU [5,55] . Cunninghan et al [56] failed to show any abnormality of disaccharidase activities in jejunal biopsies collected from patients 48 h after receiving a single intravenous dose of 5-FU. The inconsistency between the results of the present study and the Cunninghan work may be explained on the basis of the different regimen of 5-FU administration used, which induced a different pattern of histological alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animals and humans have demonstrated that severity of the structural intestinal changes induced by 5-FU is directly related to the dose and regimen used in experimental or clinical protocols. Cunninghan et al [56] observed crypt cell damage of the proximal jejunum in patients that received a single intravenous bolus of 5-FU, 48 h after treatment, but failed to show any consistent change in the mature cells of the villous, and to detect any change abnormality in the absorptive function. However, in the present study, oral administration of 5-FU, following a multiple dose regimen of 5 day/week for 4 weeks, caused severe ultrastructural alterations not only in the area of the crypt but also along the maturation-migration axis.…”
Section: Discussionmentioning
confidence: 99%
“…In the current report, the effects of Gl-PS on the intestinal epithelial barrier were investigated. Chemotherapy commonly produces structural damage to the intestinal mucosa in cancer patients [16] and causes side effects such as severe enterocolitis. In agreement with previous studies [17] , the results of the present study reveal that MTX induced small intestinal injury, which is characterized by villus shortening and fusion, epithelial atrophy, crypt loss, Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…U ltrastructural changes may be confined to the immature crypt cell pop ulation (86). Some 48 h followi ng in travenous admi n istration of mi tomycin C to rats.…”
Section: Abdominal Irradiationmentioning
confidence: 99%